Improving the Value Utilization of Tuna Peptide Powder for the Cosmetics Field Through Ozone Oxidation - Haolong Zheng; Shiyang Gu; Shiqi Huang; Yan Zhang; Feng Xu; Daofei Lv; Wenbing Yuan; Kongyu Zhu; Xin Chen (Marine Drugs)
The existing in vitro and clinical trial evidence supports the health and wellness benefits of collagen peptides sourced from various origins. Despite this, research on collagen peptides from tuna remains limited. Notably, tuna-derived peptides possess an inherent fishy odor, rendering them unsuitable for direct application in humans. This study explores the enhancement of tuna peptides’ applicability in cosmetics through odor mitigation. We developed a dual-phase ozone treatment, employing both dry and wet ozone, to deodorize tuna peptide powder, enabling its use in cosmetic formulations. The deodorized tuna peptide powder can be used in cosmetics. We optimized the ozone nitrification and deodorization conditions for tuna peptide powder by adjusting the treatment time, ozone concentration, and temperature. Sensory evaluation and GC-MS analysis confirmed the effectiveness of fishy odor removal, offering a comprehensive understanding of the deodorization process. The findings reveal that wet ozonation at 50 °C with an ozone concentration of 99.1 mg/L for 40 min significantly reduces the fishy odor of tuna peptide powder. Notably, n-Hexaldehyde, the primary odor-contributing volatile compound, decreased by 66.5%, confirming the efficacy of ozone treatment in odor mitigation. Moreover, the protein activity within the powder remained unaffected, ensuring the preservation of its functional properties. This study demonstrates the efficacy of ozone oxidation in adapting tuna peptide powder for cosmetic use.